Analisis Hukum Ekonomi Islam Tentang Transaksi Jual Beli Yang Tidak Sesuai Dengan Label Harga (Studi kasus Alfamart Sudirman 38) - Syaripudin, Enceng Iip; Zamzam, Muhammad (STAI Al Musaddadiyah Garut, 2023)
Economic development at this time has appeared many kinds of buying and selling including buying and selling in minimarkets where the contract is not spoken, buying and selling like this is called bai al-mu'athah. Buying and selling at Alfamart Sudirman 38 customers do not need to ask employees if they want to buy the goods needed. The problem in this study is: What is meant by buying and selling that does not match the price tag? How to determine a price at Alfamart? What is the view of Islamic Economic Law on buying and selling that does not match the price tag? This study aims to answer the problem of buying and selling goods that do not match the price tag. So, researchers hope that this research can be useful to be used as a reference for future researchers. This type of research is field research that covers the entirety of what happens in the field. The approach taken by this research uses qualitative research. The result of this study is the use of existing price tags that are in accordance with the provisions, but there is also deliberate use of price tags on inappropriate goods when consumers pay at the cashier. Price tags as a means of delivering information are naturally contained in price tags must be honest and not harmful. The pricing of Islamic Economic Law Analysis must meet the aspect of justice. Keywords: Islamic Economic Law, Buying and Selling, Price Tag